(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
The practice of sharia economics is growing and diverse, which has resulted in the emergence of various sharia economic disputes. This requires the development of alternative dispute resolutions, as has been done by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) by presenting Sharia Standards that specifically discuss tahkim. This paper aims to explain the provisions of tahkim in the Sharia Standards of AAOIFI and the urgency of resolving sharia economic disputes. Using the content analysis method by collecting various relevant references, this study found that various provisions must be met when carrying out a tahkim contract in the settlement of sharia economic disputes, including those relating to the pillars and requirements of tahkim, the object that is the authority of the tahkim contract, provisions for the appointment of judges, and the power of judges’ decisions. The application of the tahkim contract in the settlement of sharia economic law disputes has several advantages, namely that it is fast, cheap, efficient, energy and thought-efficient, fair, and fulfills the benefits of the disputing parties, so the development and application of tahkim as an alternative economic dispute resolution is very important.